Spontaneous extradural hemorrhage due to Langerhans cell histiocytosis of the skull in a child: A rare presentation - Bakhaidar, Mohamad G. (J Pediatr Neurosci, 2016)
Eosinophilic granuloma (EG) represents a local form of Langerhans cell histiocytosis that occurs mostly in children. It usually presents with a gradually enlarging painless skull mass, and rarely presents a rapid clinical deterioration. This 7-year-old boy who was diagnosed with EG, based on a magnetic resonance imaging scan, after presenting with a painless right parietal swelling of 7-week duration. Three weeks prior his scheduled surgery, he presented to the emergency department with a 2-day history of sudden increased of the subcutaneous swelling associated with a headache, vomiting, and decreased the level of consciousness; there was no history of trauma. Brain computed tomography revealed a right parietal bone defect with large subgaleal and extradural hematoma. He underwent emergent surgical excision of the skull lesion and evacuation of the hematoma. Histopathological examination confirmed the diagnosis of EG. We aim to raise the awareness of physicians of this rare spontaneous hemorrhagic complication of EG and review the literature.